2018
DOI: 10.1089/cbr.2018.2494
|View full text |Cite
|
Sign up to set email alerts
|

Actinium-225 for Targeted α Therapy: Coordination Chemistry and Current Chelation Approaches

Abstract: The α-emitting radionuclide actinium-225 possesses nuclear properties that are highly promising for use in targeted α therapy (TAT), a therapeutic strategy that employs α particle emissions to destroy tumors. A key factor, however, that may hinder the clinical use of actinium-225 is the poor understanding of its coordination chemistry, which creates challenges for the development of suitable chelation strategies for this ion. In this article, we provide an overview of the known chemistry of actinium and a summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 100 publications
4
134
0
2
Order By: Relevance
“…While Thiele et al recently reported on the development of an eighteen-membered macrocyclic ligand which rapidly and efficiently chelates 225 Ac at RT, no mention was made with regard to how efficiently this chelator retains the daughter isotopes of 225 Ac [14]. DOTA is probably not the most suitable chelator for 225 Ac and its daughters, however for the moment it remains the gold standard for the coordination of 225 Ac [6]. This is reflected in numerous preclinical studies involving biomolecules radiolabeled with 225 Ac via DOTA, which have shown promising results for the treatment of various cancers [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Thiele et al recently reported on the development of an eighteen-membered macrocyclic ligand which rapidly and efficiently chelates 225 Ac at RT, no mention was made with regard to how efficiently this chelator retains the daughter isotopes of 225 Ac [14]. DOTA is probably not the most suitable chelator for 225 Ac and its daughters, however for the moment it remains the gold standard for the coordination of 225 Ac [6]. This is reflected in numerous preclinical studies involving biomolecules radiolabeled with 225 Ac via DOTA, which have shown promising results for the treatment of various cancers [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Actinium-225 ( 225 Ac, t 1/2 = 9.9 days) is a highly promising α-emitter with a wide range of applications in radiotherapy of cancer mainly due to its long half-life that is well-matched for use in combination with targeting molecules, such as antibodies or nanoparticles. 225 Ac-labeled molecules have attracted increasing attention the last few years because of their outstanding properties [6]. Among these properties is the ability to induce significantly more double-strand breaks to a DNA molecule than beta (β)-particles, meaning that they are more cytotoxic [7], do not depend upon hypoxia or cell cycle considerations [8,9] and have a relatively low gamma (γ)-ray component in their decay, allowing for outpatient treatments and lower radiation doses to nuclear medicine personnel [10].…”
Section: Introductionmentioning
confidence: 99%
“…The unmetallated DOTA-MC1RL was synthesized and, since there are no nonradioactive isotopes of actinium, the analogous lanthanum-DOTA-MC1RL chelate was prepared for use as a nonradioactive control (Supplemental Figs. 4-8) (23,29). Both DOTA-MC1RL and lanthanum-DOTA-MC1RL had high binding affinity for human MC1R, 0.24 6 0.20 and 0.23 6 0.18 nM inhibition constants, respectively (Supplemental Fig.…”
Section: Synthesis and Characterization Of Parent Compound And Lanthamentioning
confidence: 93%
“…Быстро развивающимся, направлением в радионуклидной терапии является применение радиофармпрепаратов (РФП), меченных альфа-излучающими радионуклидами, которые обладают высоким потенциалом в лечении широкого круга злокачественных опухолей [5,7,27,31,33,39,45,46,51,55,58].…”
Section: Radiation Diagnostics Radiation Therapy #4 2019unclassified
“…Актиний-225 -актиноид, период полураспад 10 дней, при альфа-распаде образует три альфа-излучающих радионуклида: франций-221 (Т 1/2 = 4,8 мин), астат-217 (Т 1/2 = 32,3 мсек) и висмут-213 (Т1/2 = 45,6 мин), что делает его очень эффективным и потенциально оптимальным для ТАТ. 225 Ас может быть получен как в результате распада урана-233, так и в циклотроне [11,18,56]. При наработке 225 Ас на ускорителе также образуется 227 Ас, который имеет период полураспада 21,77 лет.…”
Section: Radiation Diagnostics Radiation Therapy #4 2019unclassified